Anticancer effect of different rhizome extracts of the Lebanese Rheum ribes L. species on colorectal cancer cell lines - Batoul Al-Khatib; Akram Hijazi; Nafez Hareb; Mona Diab-Assaf; Racha Karaky (Elsevier, 2022)
Introduction: Colorectal cancer is the second leading cause of cancer-related mortality. Rheum ribes L. is one of the most important medicinal plants showing several biological activities. Few studies demonstrated anticancer potential of extracts of Turkish and Iranian Rheum ribes L. species rhizomes. We report for the first time the anticancer activity of different types of extracts of the rhizomes of the Lebanese Rheum ribes L. species against colorectal cancer cell lines. Methods: Five types of extracts were prepared using different solvents and cytotoxicity was assessed on colorectal cancer cell lines. Ethanolic and dichloromethane extracts were chosen for further studies and their effects on cell proliferation (MTT assay and trypan blue exclusion assay), colony forming ability (colony formation in soft agar), migration (scratch wound assay), and adhesion were assessed. Results: Our results showed that ethanolic and dichloromethane extracts reduce HT-29 and HCT-116 cell viability in a dose and time dependent manner. They are also able to decrease colony-forming ability of these cells in soft agar medium. This anti-proliferative effect was accompanied by an increase in PARP cleavage suggesting a proapoptotic effect. Moreover, these extracts were also able to inhibit HT-29 and HCT-116 cell adhesion and migration suggesting their ability to reduce metastatic dissemination. Conclusion: These findings suggest a high therapeutic potential of the extracts of rhizomes of the Lebanese Rheum ribes L. species in the treatment of colorectal cancer.